Respon Lembaga Pendidikan Formal Berbasis Pesantren pada Masa Pandemi - Nia Anggraini; Moh. Turmudi (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The outbreak of the Covid-19 pandemic has hampered education in Indonesia, resulting in changes to the curriculum and learning media. This change is the most crucial factor so that teaching and learning activities can be carried out, achieve educational goals and educate the nation. The researcher aims to determine the response of Islamic boarding school-based formal education during the pandemic. In this study, the type of qualitative research is descriptive analysis. The data collection carried out in this study was using interview, observation and documentation techniques. Analysis of the data used is a flow model. The results of this study stated that the curriculum and learning media underwent very urgent changes in response to the pattern of life and social order during the Covid-19 pandemic.